Does the incremental shuttle walk test require maximal effort in young obese women? - Jürgensen,S.P. (2016)
Obesity is a chronic disease with a multifaceted treatment approach that includes nutritional counseling, structured exercise training, and increased daily physical activity. Increased body mass elicits higher cardiovascular, ventilatory and metabolic demands to varying degrees during exercise. With functional capacity assessment, this variability can be evaluated so individualized guidance for exercise training and daily physical activity can be provided. The aim of the present study was to compare cardiovascular, ventilatory and metabolic responses obtained during a symptom-limited cardiopulmonary exercise test (CPX) on a treadmill to responses obtained by the incremental shuttle walk test (ISWT) in obese women and to propose a peak oxygen consumption (VO2) prediction equation through variables obtained during the ISWT. Forty obese women (BMI ≥30 kg/m2) performed one treadmill CPX and two ISWTs. Heart rate (HR), arterial blood pressure (ABP) and perceived exertion by the Borg scale were measured at rest, during each stage of the exercise protocol, and throughout the recovery period. The predicted maximal heart rate (HRmax) was calculated (210 – age in years) (16) and compared to the HR response during the CPX. Peak VO2 obtained during CPX correlated significantly (P<0.05) with ISWT peak VO2 (r=0.79) as well as ISWT distance (r=0.65). The predictive model for CPX peak VO2, using age and ISWT distance explained 67% of the variability. The current study indicates the ISWT may be used to predict aerobic capacity in obese women when CPX is not a viable option.